Theory and Practice on Building Global City with Chinese Characteristics: Beijing as a Case - Kaizhong Yang; Han Liang (European Regional Science Association (ERSA), 2012)
The paper summarizes the concept of Global city with Chinese characteristics from a comparative perspective, points out that the Chinese emphasis on global cities influence and competitiveness, which is different from the command and control function stressed by the Western. Taking Beijing as a case, we reveals systematically that the development of Chinese global cities faces three traps: the comparative advantage of primary element, economies of scale of physical investments expansion, and high risks of innovations for high costs, and the intensification of them trigger the developing global city disease. Then we propose basic strategies and routines for overcoming the traps and promoting global cities in China.
Keywords: 330